2011
DOI: 10.1074/jbc.m110.187849
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Up-regulates ATBF1 Transcription but Causes Its Protein Degradation in Estrogen Receptor-α-positive Breast Cancer Cells

Abstract: The proper level of estrogen-estrogen receptor (ER) signaling is important for the maintenance of epithelial homeostasis in the breast. In a previous study we demonstrated that ATBF1, which has been suggested as a tumor suppressor in breast cancer, inhibited estrogen-mediated cell proliferation by selectively competing with AIB1 for binding to the ER. However, the expression of ATBF1 mRNA was shown to positively correlate with ER in breast cancer specimens. We, therefore, examined whether estrogen regulates AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 57 publications
2
48
0
Order By: Relevance
“…In mouse mammary glands, we previously demonstrated that Zfhx3 mRNA expression varies at different stages during development, reaching the highest level at lactation (20), and that Zfhx3 regulates pubertal mammary gland development (20). In addition, both estrogen and progesterone, two hormones essential for normal mammary gland development, induce or enhance the transcription of ZFHX3 in human and mouse mammary epithelial cells (21,22), although estrogen also causes protein degradation of ZFHX3 when too much estrogen is present (21). Taken together with the observation that deletion of Zfhx3 in mouse prostates alters the transcription level of Prlr (17), a key regulator of lactogenic differentiation in the mammary gland, we hypothesize that ZFHX3 is more relevant to lactogenic differentiation during mammary gland development.…”
mentioning
confidence: 99%
“…In mouse mammary glands, we previously demonstrated that Zfhx3 mRNA expression varies at different stages during development, reaching the highest level at lactation (20), and that Zfhx3 regulates pubertal mammary gland development (20). In addition, both estrogen and progesterone, two hormones essential for normal mammary gland development, induce or enhance the transcription of ZFHX3 in human and mouse mammary epithelial cells (21,22), although estrogen also causes protein degradation of ZFHX3 when too much estrogen is present (21). Taken together with the observation that deletion of Zfhx3 in mouse prostates alters the transcription level of Prlr (17), a key regulator of lactogenic differentiation in the mammary gland, we hypothesize that ZFHX3 is more relevant to lactogenic differentiation during mammary gland development.…”
mentioning
confidence: 99%
“…The ZFHX3 gene has been associated with growth and differentiation regulation of several tissues, such as neuron and skeletal muscle (Jung et al 2005). Although the function of the ZFHX3 gene in cardiac tissue is unknown, it was expressed in mouse hearts (Dong et al 2011). The ZFHX3 gene variants are associated with atrial fibrillation in a Chinese Han population (Sun et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…T-47D cells were seeded in 24-well plates at 1 Â 10 5 cells per well. On the next day, cells were transfected with the ATBF1 promoter reporter plasmids constructed in our previous study [16] in regular medium. One day after transfection, cells were treated with 100 nM Pg for 12 h or 36 h, and luciferase activities were measured using the dual luciferase reporter assay system (Promega, Madison, WI).…”
Section: Dual Luciferase Assaymentioning
confidence: 99%
“…Promoter-luciferase reporter assay was performed as previously described [16,20]. T-47D cells were seeded in 24-well plates at 1 Â 10 5 cells per well.…”
Section: Dual Luciferase Assaymentioning
confidence: 99%
See 1 more Smart Citation